Developing innovation innovation management in IT companies - Buljubašić, Tomislav (Walter de Gruyter GmbH, 2020)
One of the greatest challenges in the ever-changing world of IT is to create and maintain an innovation culture and align innovation activities with company strategy. This book provides a fresh perspective on innovation management activities in an IT environment using examples from both start-ups and established companies such as Cisco, Ericsson Nikola Tesla, Lufthansa Systems, Worldline, Amdocs, Telefonica and Enea. This book addresses the following issues: The software development environment offers many possibilities for innovation, yet also places some constraints on the innovation process at the same time. It considers how this can be bypassed to bring success to the company. It is a challenge to create and maintain an innovation culture using an agile process in the area of software development with its short cycles. This book describes how to bring innovation challenges closer to developers and use their experience and vision to create new projects. It also shows how to inspire software engineers using incremental and often small but useful money-saving improvements. The fourth industrial revolution changes companies from the inside and brings changes to common agile product management processes in IT. This book examines the effects on innovation management and what mechanisms are used for success in this new environment.